INNOVATION IN WRESTLING EDUCATION: HARNESSING TECHNOLOGY FOR ATHLETE PERFORMANCE ENHANCEMENT - Juhanis; M. Adam Mappaompo, M. Imran Hasanuddin, Muhammad Qasash Hasyim (International Journal of Teaching and Learning, 2024)
The use of innovative teaching methods in wrestling has proven essential to improving athlete performance. This article explores how technology use can contribute significantly to the development of wrestling athletes. We investigate how technology can be incorporated into wrestling education and training, with an emphasis on performance enhancement. In-depth technical analysis, real-time health monitoring, and the creation of more complex gaming strategies are made possible by the utilization of wearable sensors, interactive learning apps, and video analysis. Virtual match simulations and mental technology also add another level of training for athletes' psychological and tactical needs. This article also addresses potential drawbacks to these developments, such as budgetary constraints and incorporating technology into sports education. This investigation has allowed us to better understand how technology can influence wrestling education going forward and improve the performance of athletes.